Breaking the fragile. The experience of urban growth in the steppes of amancaes - Soria Dall’Orso, Carlos (2019)
This paper introduces the reader into the interdisciplinary nature of environmental law, through the review of a case of green areas ecosystem degradation by Lima’s city urban growth. The authors show the usefulness of using history, urban planning, environmental policy, environmental management tools, criminal prosecution, among other disciplines, in order to apply the legislation in a coherent manner and oriented to contribute to the common well-being. The integration of these multiple approaches in the Sustainable Development Goals by 2030, allows fi nancing for projects help overcome the challenges in order to reconcile urban growth and urban green areas conservation.